ANALYSIS OF EXISTING METHODS FOR PREVENTING COMPLICATIONS AFTER DISTAL PANCREATECTOMY - Лубянский, Владимир Григорьевич; Сероштанов, Василий Владимирович; Худякова, Влада Игоревна (Medicine in Kuzbass, 2025)
Distal pancreatectomy accounts for approximately one-third of all pancreatic surgeries. Despite the existing technological capabilities for performing the procedure safely, it remains associated with a high rate of serious postoperative complications. The aim of the research – To analyze the efficacy and safety of distal pancreatectomy with spleen preservation and to assess the impact of this technology on the incidence and structure of postoperative complications compared to traditional distal pancreatectomy with splenectomy. Materials and Methods. The results of distal pancreatectomy in patients with chronic pancreatitis and pancreatic tumors were analyzed. Portal venous blood flow was assessed preoperatively and postoperatively. Results. Distal pancreatectomy with splenectomy is associated with complications in the early postoperative period. However, spleen preservation during distal pancreatectomy helps prevent complications. The state of blood circulation in the portal and splenic veins was studied using duplex scanning. Conclusion. The use of spleen-preserving technology improves the results of distal pancreatectomy in patients with benign pancreatic tumors and chronic pancreatitis. In some cases, videolaparoscopic technologies for distal pancreatectomy can be used.